Isolation of transketolase gene, subcellular localization, and transketolase protein structure studies of sugarcane (Saccharum officinarum. L) - Kalhori, Nahid (2013)
This study focused on isolation, identification, subcellular localisation, protein structure prediction of transketolase enzyme from sugarcane, Saccharum officinarum. Pentose phosphate pathway is composed of two functionally-connected phases, the oxidative and non-oxidative phase. Both phases are catalysed by a series of enzymes. One of these enzymes is transketolase which play an important role in non-oxidative phase of pentose phosphate pathway (PPP). Synthesis of sugar phosphate intermediate is the main role of this enzyme in non-oxidative phase of pentose phosphate pathway. Transketolase transfer two carbon units from fructose- 6-phosphate to erythrose-4-phosphate and convert two carbon fragments from glyceraldehyde-3-phophate (G3P) to ketose of xylulose-5-phosphate. Erythrose-4- phosphate then enters the shikimate pathway that produced many secondary metabolites such as aromatic amino acids, lignin and flavonoid. Transketolase also play important role in photosynthesis and glycolysis. Although the contribution of transketolase in plant system is important, study of this enzyme is still limited. Until now, TKT genes had been isolated only from seven plants so far, thus this leads to the first objective to isolate TKT gene from sugarcane to compare its identity with other organisms. Unlike bacteria, fungi and all animals, PPP is complete in the cytosol of these living system and all enzymes of this pathway localised in the cytosol. However, in plant system, the first phase of pentose phosphate pathway is complete in the cytosol of plant and the sub localisation for non-oxidative pentose phosphate pathway in still remains unclear. Thus, the second objective is to determine its subcellular localization of sugarcane transketolase. The final objective is to predict modelling protein structure of sugarcane transketolase. The isolation of TKT by was done by RT- PCR, followed by cloning and sequencing. The present study has isolated 2327 bp length of sugarcane TKT. Similarity studies using CLUSTALW2 revealed that sugarcane TKT gene showed highest identity with Zea mays (99%). Classification analysis revealed that both plants are in the same family, Poaceae. However, the identity of sugarcane TKT compared with other plants species are low (<65 %) due to these plants are only in the same phylum, Strephytophyte. Moreover, sugarcane TKT showed lower similarity (<60%) compared with bacteria, yeast and animals because these organisms from different kingdom, animalia. Analysis by Target P 1.1 followed by Chloro P revealed that sugarcane transketolase is localised in the chloroplast which is 85 amino acids are plant plastid target sequence. The nucleotide sequence of sugarcane TKT was converted to amino acid sequence using Expasy.org, Phyre2 and YASARA to predict secondary, tertiary structure and the quality of protein structure of sugarcane transketolase. This present study revealed that sugarcane transketolase protein is 100% similarity with Thiamin diphosphate-binding fold, from Zea mays (d1itz). In conclusion, sugarcane transketolase was successfully isolated and was found plastidic in plant system. This led to conclusion that the OPPP is incomplete in the cytosol of sugarcane. This present study also similarity sequence of sugarcane TKT closely related with classification or taxonomy level of plants and other organisms. This present study also found that sugarcane transketolase protein is 100% similarity with Thiamin diphosphate-binding fold, from Zea mays (d1itz).